Critters of Maine pocket guide - McCarthy, Ann E.; Wildlife Forever (Organization) (Cambridge, Minn. : Adventure Publications, 2002)
A field guide of Maine mammals, birds, spring peeper, spotted salamander, common garter snake, painted turtle and snapping turtle.
Keywords: Zoology -- Maine -- Pictorial works; Zoology -- Maine -- Guides; Animals -- Identification; Maine -- Fish and wildlife